Digital Emotional Bonds: How Virtual Anchor Characteristics Drive User Purchase Intention in Livestreaming E-commerce - Yiwei Zhao; Wonjun Chung (SAGE Open)
In the digital era, livestreaming e-commerce has emerged as a new frontier in the industry due to its unique advantages. However, human anchors face time, energy, and sustained high-intensity output limitations. The emergence of virtual digital personas offers a new solution for the livestreaming e-commerce industry. Unlike human anchors, virtual anchors possess advantages such as greater controllability, high personalization, and 24/7 uninterrupted livestreaming, making them favored by platforms. While the industry continues to increase the practical application of virtual anchors, academic exploration of their mechanisms in influencing consumer purchasing behavior remains insufficient, necessitating theoretical and empirical responses. Based on the Stimulus-Organism-Response (S-O-R) theoretical framework, this study investigates the impact of virtual anchor characteristics (visibility, metavoicing, guidance shopping, and trading) on consumer purchase intention and its internal mechanisms. Data was collected through questionnaires, yielding 441 valid responses. The Partial Least Squares (PLS) method was used for data analysis. The results show that the visibility, metavoicing, and guidance shopping of virtual anchors significantly positively influence consumer purchase intention through brand authenticity, brand attachment, and sense of community. However, trading only affects purchase intention through brand attachment and sense of community, with the mediating effect of brand authenticity being insignificant. This study extends the application of S-O-R theory in the context of virtual anchors, enriches the theoretical understanding of how virtual service providers influence consumer behavior, and provides practical insights for optimizing virtual anchor images in livestreaming e-commerce.